PENDEKTEKSIAN PERUBAHAN TOPOGRAFI KUBAH LAVA MENGGUNAKAN CITRA OPTIS RESOLUSI TINGGI DAN RADAR UNTUK PREDIKSI LONGSORAN VOLKANIK (STUDI KASUS GUNUNG IBU) - Ayu Anas, Nur
One of the volcanoes with a lava dome is Mt. Ibu, located in North Maluku Province, Indonesia. In the case of Mt. Ibu, monitoring the growth of the lava dome only relies on cameras at observation posts. Therefore, to overcome this problem, in this study PlanetScope optical imagery, Sentinel-1A radar imagery, and ALOS PALSAR are used to monitor changes in the topography of the lava dome and predict volcanic avalanches. The results show that Mt. Ibu has experienced a change in the topography of the lava dome because, based on calculations, the lava dome area has increased from 0,059 km2 in 2020 to 0,832 km2 in 2022. Then the volume calculations show that the lava dome volume has increased from 0,0005 km3 in 1999 to 0,070 km3 in 2022. Based on the prediction results using the Autoregressive Integrated Moving Average (ARIMA) and Seasonal Autoregressive Integrated Moving Average (SARIMA) models, estimation of the lava dome will fill the outer crater in 2037 with an area of 1,477 km2 and a volume of 0,114 km3; at this time, it is predicted that volcanic avalanches will occur if there are no external or internal factors that occurred. Internal factors that can trigger topographic changes and landslides include increased magmatic activity as indicated by the frequency of earthquakes, eruptions, deep volcanic and shallow volcanic that. External factors include the discharge of lava flows and lava collapse as indicated by high surface roughness based on the Normalized Radar Cross Section (NRCS) of around -10,211 to 0,6 dB, high surface deformation based on the Pair-wise Logic Technique Differential Interferometric Synthetic Aperture Radar (PLT D-InSAR) with the highest subsidence value of -0,48 m and uplift of 0,667 m, and high lineament density based on the modified Segment Tracing Algorithm (mSTA) with values of ???????? ± 4,5 km-1, ???????? ± 8 km-1, and ???????? ± 3,8km-1, shows that the lava dome has a weak zone that can trigger volcanic avalanches. Then based on these parameters, the zone area of the volcanic avalanche area is on the lava dome and the northern flank.